PERJALANAN TEKNIK REKAMAN STEREOFONIK PADA KARAWITAN JAWA - Iwan Budi Santoso (Institut Seni Indonesia Surakarta, 2021)
The touch between karawitan and recording technology produce karawitan recording based on stereophonic forms. Stereophonics is a form of the next generation of monophonics recording. Monophonics has a single-track or single- sound while stereophonics emphasizes two-track recording. The recording technique with stereophonics eventually became the main choice in the development of music recording because it is able to bring the sound of music closer to the original. A stereophonic development for karawitan recording does not eventually begin. It is through the stages of time that finally stereophonic recording technology is used in Javanese karawitan recording.